Automated Image Analysis of Live/Dead Staining of the Fungus Aureobasidium pullulans on Microscope Slides and Leaf Surfaces - Christopher D. Nelson; Russell N. Spear; John H. Andrews (BioTechniques)
An image analysis program and protocol for the identification and enumeration of live versus dead cells of the yeast-like fungus Aureobasidium pullulans was developed for both populations on microscope slides and leaf surfaces. Live cells took up CellTracker Blue™, while nonviable cells stained with DEAD Red™. Image analysis macro programs running under Optimas™ software were used to acquire images and to differentiate and enumerate viable from nonviable cells. The software was capable of discriminating green as a third parameter for identification and quantification of green fluorescent protein-expressing cells in a wild-type population.